(untitled) (Scientific journal of the Fergana State University, 2024)
This species has been used in folk medicine for over 2000 years as a medicinal plant against liver, kidney, rheumatism, gastrointestinal and heart diseases. In modern medicine, it is widely used as a protective agent against biological and chemical poisoning. This article provides information on the chemical composition of the medicinal plant, its importance in folk and modern medicine, as well as the use of drugs prepared from its various organs.